Penggunaan Template Study Planner untuk Menunjang Proses Self-Directed Learning - Sebuah Studi Literatur - Halimah Thania Nasution; Gandes Retno Rahayu; Tridjoko Hadianto (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: Self-directed learning is a form of independent learning where in the process it is advisable that students create a study planner so that the learning process is more focus and effective. A study planner can be used as a reference that will assist students in evaluating and reflecting the learning process. This study aimed to find out how the application of study planner can support the process of self-directed learning, this will be based on a literature study.Method: This research was in the form of a literature study which covered the application of study planner and its relation to self-directed learning. The literature searches were conducted with two databases (e-sources national library and ERIC), by using 11 keywords, in order to obtain more amounts of readings available, that were in relation to the utilization of study planner in order to support self-directed learning. Based on five inclusion and exclusion criteria were used to select 22 journals that obtained from the results of database searches, two journals that can be used to answer research questions were found. Data were extracted systematically by segmenting and coding. Followed by determining patterns to find broader category. Results: Based on segmenting and coding process and determining important patterns, two broad categories were found, that are (1) The benefit of study planner in self-directed learning; and (2) Factors that affect study planner and self-directed learning.Conclusion: Study planner can assist students in developing their self-directed learning skills, that will be handy to support their lifelong learning skills. Study planner can also give motivations to students in performing self-directed learning